THE ORIGIN OF PERSONAL NAMES IN RUSSIAN ANTHROPONYMY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, the observed types of onomastic units are analyzed on the basis of their respective names. Semantic, grammatical, orthographic features of hidden notes are considered, and the necessity to take into account their uniqueness is emphasized in their study.